2017
DOI: 10.21809/rilemtechlett.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Steel corrosion in reinforced alkali-activated materials

Abstract: The development of alkali-activated materials (AAMs) as an alternative to Portland cement (PC) has seen significant progress in the past decades. However, there still remains significant uncertainty regarding their long term performance when used in steel-reinforced structures. The durability of AAMs in such applications depends strongly on the corrosion behaviour of the embedded steel reinforcement, and the experimental data in the literature are limited and in some cases inconsistent. This letter elucidates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 43 publications
5
56
1
1
Order By: Relevance
“…These values are in line with previous observations and indicate that in both materials, alkali‐activated fly ash mortar and Portland cement mortar, the steel had attained the passive state during curing. [ 9,21 ] The ohmic resistances ( R el ) after curing were 500–600 Ω for the Portland cement mortar specimens and ~400 Ω for the alkali‐activated fly ash mortar (Figures S1–S4), indicating a finer pore structure and possibly a lower ionic strength of the pore solution in the Portland cement mortar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These values are in line with previous observations and indicate that in both materials, alkali‐activated fly ash mortar and Portland cement mortar, the steel had attained the passive state during curing. [ 9,21 ] The ohmic resistances ( R el ) after curing were 500–600 Ω for the Portland cement mortar specimens and ~400 Ω for the alkali‐activated fly ash mortar (Figures S1–S4), indicating a finer pore structure and possibly a lower ionic strength of the pore solution in the Portland cement mortar.…”
Section: Resultsmentioning
confidence: 99%
“…While extensive data regarding the critical chloride content in concretes and mortars based on Portland cement and blended cement have been compiled, [ 6–8 ] much less data in this regard are available for concretes or mortars based on alkali‐activated binders. [ 9 ] Early work showed that carbon steel in chloride‐free alkali‐activated fly ash mortars attains a passive state and indicated that chloride contents up to 0.4 wt% with respect to binder (wrtb) do not cause steel corrosion in these mortars. [ 10 ] The authors of a more recent study [ 11 ] concluded that the critical chloride content for the onset of steel corrosion in alkali‐activated fly ash mortars is in the range 1–1.7 wt% wrtb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For BFS and WPS mortars, the sulfide supplied by the slag was released and altered the passive film into a sulfidic layer that has a different electrochemical response (Mundra et al, 2017a). Therefore, the combination (R f -CPE f ) was not observed, except when they were exposed to standard laboratory conditions or when WPS mortar was immersed in the alkaline solution at early ages.…”
Section: Resultsmentioning
confidence: 99%
“…During the hydration of PC, portlandite [Ca(OH) 2 ] forms as an important hydration product, and plays important role in delaying the onset of the corrosion of embedded steel, as it can maintain the high pH of the cement pore solution through a buffering mechanism (Bertolini et al, 2013). However, in AAMs portlandite is not typically identified as a reaction product (Lloyd et al, 2010), and therefore, the availability (or conversely, leaching) of OH − ions from the pore solution at the steel-concrete interface will have a greater influence in ensuring the stability of this protective layer in AAMs (Mundra et al, 2017d).…”
Section: Introductionmentioning
confidence: 99%